Impact Factors of Use of Integrated Non-communicable Diseases Development Post at Community Health Centers - Frischa Valentina; Lita Sri Andayani; Rahayu Lubis (Randwick International of Social Science Journal, 2023)
Integrated Non-communicable Diseases Development Post or called Posbindu PTM arises from human behavior such as smoking, unhealthy diet, lack of physical activity and consumption of alcoholic beverages. PTM is a public health problem that causes morbidity, disability and death. PTM often goes undetected because it is asymptomatic and has no complaints, when it is found it is already at an advanced stage making it difficult to cure and resulting in disability or death. PTM is the main cause of death globally, based on data from the World Health Organization (WHO) showing that in 2016, out of 57 million deaths that occurred in the world, 41 million deaths (70%) were caused by PTM. PTM is the biggest cause of death, namely cardiovascular disease, cancer, chronic respiratory disease and diabetes. Based on data from PUSKESMAS or Public Health Center Rantauprapat City, Labuhanbatu Regency, the number of Posbindu PTM visits in 2018 was 606 visits, while in 2019 there was a significant increase of 1246 visits. The aim of the study was to determine the factors that influence the utilization of the Non-Communicable Diseases Integrated Development Post (POSBINDU PTM) at the PUSKESMAS or Public Health Center Rantauprapat, Labuhanbatu Regency. This research is a quantitative study with a Cross Sectional Study design. Data analysis used the chi-square test with a sample of 127 respondents. The results showed that the related variables were Knowledge (p=0.001), Attitude (p=0.001), Facilities Support (p=0.045) and Family Support (p=0.028) with the Utilization of Posbindu PTM.